ANALYZE THE PRONUNCIATION OF PHONETIC SYMBOLS IN ENGLISH - Khairani, Lutfi Putri; Tanjung, Rahmi Rahmita; Lubis, Yani (Peneliti.net, 2023)
This article examines the phonetic symbols of pronunciation with the aim of explaining and describing how the correct sound sounds in the phonetic symbols of a word or sentence. This type of research is descriptive qualitative and its design directs the research to investigate or describe social situations that are studied in depth, breadth, and depth. In our research, we understand the material understanding that many people do not know and do not understand well.